(untitled) (Indian Journal of Animal Production and Management, 2024)
A study was conducted on eighteen SVVU T-17 grower pigs of 3 months age with similar body weights, and were divided into three groups with 6 pigs in each group for a period of 60 days to study the effect of inclusion of turmeric and ginger supplementation @ 1% in the basal diet on the haemato biochemical profile. The study revealed that among the haematological parameters Hb and PCV exhibited significantly higher values with in the physiological range in turmeric group compared to other groups. Among several biochemical parameters observed under the study, ALT and AST were exhibited significant decrease in turmeric and ginger groups. Total protein, albumin, globulin levels were in similar range with control group. Cholesterol exhibited significant decrease in turmeric and ginger groups compared to the control group. Turmeric and ginger had hepato-protective nature and a positive effect on overall health performance. Especially, turmeric had direct positive effect on haemato-biochemical profile when compared to the other groups.